Performance evaluation of 2 channels, 4 channels and 8 channels optical fiber communication system at l0GBits per second per channel on DWDM structure / Mazura Abas - Abas, Mazura (2014)
Dense Wavelength Division Multiplexing (DWDM) is an optical transmission technology that enables significant increases in the data rate that can be carried over a single optical fiber by use of multiple wavelengths, each carrying a separate channel. Multiple channel communication system utilizing fiber optics was designed and performance evaluations was measured, analyzed and reported. Performance evaluation was evaluated through measurement of bit error rate (BER), Q factor, power received and signal power by using dispersion compensating fiber (DCF) and without dispersion compensating fiber on a single mode fiber. Variations of wavelength and fiber length were used to investigate the optimum system criteria.